Pengaruh Taraf Filtrat Abu Sekam Padi (FASP) Ditambah Urea Terhadap Ph, Konsentrasi VFA Dan NH3 Tongkol Jagung Secara In Vitro - Intan Lawalu; Luh Sri Enawati; Gustaf Oematan (Animal Agricultura, 2026)
The research objective was to determine the effect of the level of filtrate rice husk ash plus urea on the pH, the concentration of VFA and NH3 corn cobs in vitro, this research method used is an experimental method with a basic design of completely randomized design (CRD) consisting of 6 treatments with 3 replications, thus this study uses 18 experimental units. The treatment in this study is R0; corn cobs without FASP added with 4% urea, R1: corn cobs added with FASP 5% and 4% urea, R2: corn cobs added with FASP 10% and 4% urea, R3: corn cobs added with FASP 15% and 4% urea, R4: corn cobs added with FASP 20% and 4% urea, R5: corn cobs added with FASP 25% and 4% urea. Data were analyzed by analysis of variance and Duncan's test. The parameters observed were the pH, the concentration of VFA and NH3 in vitro. The average value of each variable in each treatment is the pH R0 (7.10), R1 (7.00), R2 (6.85), R3 (6.73), R4 (6, 77), R5 (6.88). The concentrations of VFA (mM) are R0 (106.28), R1 (118.10), R2 (141.08), R3 (148.45), R4 (144.25), R5 (131.33). The concentrations of NH3 (mM) are R0 (17.96), R1 (37.80), R2 (38.04), R3 (51.71), R4 (42.68), R5 (40.71). The results of statistical analysis showed that the effect of the level of filtrate rice husk ash plus urea had a very significant effect (P<0.01) on the degree of acidity (pH), a significant effect (P<0.05) on VFA and no significant effect (p>0.05) on NH3. This it was concluded that the effect of the level of FASP plus urea had a varying effect on the pH, the concentration of VFA and NH3 in vitro in corn cob flour.